Grain Sorghum Cost-Return Budget in North Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2006)
This publication provides estimated cost and returns for forward farm planning for grain sorghum in north central Kansas.
MF2159_2006_10
Keywords: MF2159; Crops; Economics; MF